Proceedings of the International Workshop on Mechanical behavior of thick composites : March 14-15, 2016, Montreal, Quebec, Canada - Hoa, S. V. (DEstech Publications, 2016)
Book presents investigations into the behavior of higher-ply laminated composites in a variety of shapes. The focus is on technical methods and discoveries regarding how thick composites react to loads and stresses, especially with regard to damage initiation and failure. Models and data explained in the book are used for analyzing the internal structure, materials and interface of thick composites, with a number of recent examples drawn from aircraft components, specifically, helicopter parts. Keywords: thermal field, Hashin failure criteria, thick woven composite, aramid-epoxy, contact mechanics, pin and cylinder, Si-C coated C-fiber reinforced Ti-MMC composite, delamination, bolt loads, through-the-thickness stress, crack initiation, helicopter blade, rotor yoke, jet fan containment, Fiber Bragg Grating, carbon fiber sensor, flexural fatigue, glass fiber reinforced (GFRP).
"Sponsors: Concordia University; Bell Helicopter; AHS Montreal Ottawa; CRIAQ; Concordia Centre for Composites; Indian Institute of Science (IISc)."
Keywords: Composite materials -- Congresses.; Composite materials -- Mechanical properties -- Congresses.; elektronické knihy; electronic books